Clinically recorded cortical auditory evoked potentials from paediatric cochlear implant users fitted with electrically elicited stapedius reflex thresholds. (May 2018) - Kosaner, Julie; Van Dun, Bram; Yigit, Ozgur; Gultekin, Muammer; Bayguzina, Svetlana
Abstract: Objectives: This study aimed to objectively evaluate access to soft sounds (55 dB SPL) in paediatric CI users, all wearing MED-EL (Innsbruck, Austria) devices who were fitted with the objective electrically elicited stapedius reflex threshold (eSRT) fitting method, to track their cortical auditory evoked potential (CAEP) presence and latency, and to compare their CAEPs to those of normal-hearing peers. Methods: Forty-five unilaterally implanted, pre-lingually deafened MED-EL CI users, aged 12–48 months, underwent CAEP testing in the clinic at regular monthly intervals post switch-on. CAEPs were recorded in response to short speech tokens /m/, /g/ and /t/ presented in the free field at 55 dB SPL. Twenty children with normal hearing (NH), similarly aged, underwent CAEP testing once. Results: The proportion of present CAEPs increased and CAEP P1 latencies reduced significantly with post-implantation duration. CAEPs were scored based on their presence and age-appropriate P1 latency. These CAEP scores increased significantly with post-implantation duration. CAEP scores were significantly worse for the /m/ speech token compared to the other two tokens. Compared to the NH group, CAEP scores were significantly smaller for all post-implantation test intervals. Conclusions: This study provides clinicians with a first step towards typical ranges of CAEP presence, latency, and derived CAEP score over the first months of MED-EL CI use. CAEPs within these typical ranges could validate intervention whereas less than optimum CAEPs could prompt clinicians to seek solutions in a timely manner. CAEPs could clinically validate whether a CI provides adequate access to soft sounds. This approach could form an alternative to behavioural soft sound access verification.